The Learning and Service Experience as a Tool for Raising Local Leaders - Ramos-Arriagada, R (UNIV LA SALLE, 2018)
The purpose of the experience reported in this paper was to strengthen the social entrepreneurship of students from two courses of the Accounting and Audit program at Universidad de Santiago de Chile, by reinforcing the soft skills required by the educational model, via the implementation, over the course of a semester, of the teaching methodology of learning and service. Each course chose a beneficiary community: One course worked with only one beneficiary, while the other was split among independent groups. The students decided and scheduled all the required actions. An analysis of the obtained results revealed, in particular, some striking appraisals at a personal level, about their professional future, and about the reality of education in Chile; they weighed the business influence in the socioeconomic environment in which they worked and the importance of collaborative work; they compared their own reality with that of people in need; they recognized that they overcame the initial distrust and turned it into pride, knowing they are capable of helping others, despite being students; they found that they could be social leaders. The conclusions imply a change of paradigm in university education: the application of an active teaching methodology causes an impact between students and third parties.